Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content 1. Managing the Archaeological Records: Present Practices and Future Trends Co-Prof. Mohammed Ali Al-Belushi 2. The role of the mobile museum in promoting National Identity and the Background Kingdom of Saudi Arabia Co-Prof. Noha Saeed Nagaiti, Mrs. Mrouj Hatem Qurban 3. The Representation of the Social and Political Reality in the Palestinian Cinema: Mashrawi’s film "Laila’s Birthday" Dr. Ghada Hamdi Alraee 4. Research data management and its role in developing scientific research Mrs. Tahani Mohammed Mousa 5. The role of the Herzliya Institute in Israeli decision-making Dr. Elham Jabr Salm Shamali, Mrs. Nedaa Mohamad Kishko 6. The Level of Effectiveness of Social Upbringing Methods in Promoting Public Taste of Saudi Society (An Applied Study on a Sample of Male and Female Teachers in the City of Dammam in the Eastern Region of Saudi Arabia) Mrs. Albanderi Saad Alqahtani, Dr. Olfa Ahmed Mejri 7. The role of the United Nations in protecting the rights of refugee children (An analytical study) Mrs. Sarah Mohammed Al-Qahtani, Dr. Rawa Ghazi Al-Makki 8. Sociological analysis to the communicative technological system Maitreconference Zenkoufi Fouzia Bent Mahmoud , Dr. Korzet Najima Bent Abd Elkader